Ammonia nitrogen exposure caused structural damages to gill mitochondria of clam Ruditapes philippinarum - Ming Cong; Yuanmei Li; Hongchao Xu; Jiasen Lv; Huifeng Wu; Ye Zhao (Ecotoxicology and Environmental Safety, 2021)
Ammonia nitrogen has been one of the key pollution indicators along the Chinese coastline for quite a few years. Our previous studies have proved that ammonia nitrogen is harmful for Ruditapes philippinarum clam in several aspects. Environmental concentrations of ammonia nitrogen were found to significantly decrease ATP contents and disturb ATP metabolism, in addition to reducing the potential across the mitochondrial membrane in clam gill tissues. Accordingly, mitochondrion is considered as one of the target organelles of ammonia nitrogen toxicity in clams. However, there is a lack of direct evidence to prove it. In order to reveal detail information of ammonia nitrogen toxicity on clam mitochondria and screen the related biomarker to indicate ammonia nitrogen pollution, mitochondrial parameters in gill tissues including swelling, mtDNA copy number and marker enzyme (succinic dehydrogenase, SDH) activity were measured after the clams were exposed to 0.1 mg/L and 0.5 mg/L ammonia nitrogen for 3 days and 21 days, respectively. Moreover, adverse effects of ammonia nitrogen exposure on clam mitochondrial ultra-structures, mitochondrial swelling and division were also discriminated under transmission electron microscope (TEM). Final results showed that ammonia nitrogen exposure to both concentrations significantly induced mitochondrial swelling, reduced the number of mitochondria and messed their normal structure, decreased the number of mtDNA copies and down-regulated SDH activity, all in a concentration and duration dependent manner. So, the present study helps us to better understand the structural damage of ammonia nitrogen on mitochondria in clam gill cells and provides fundamental data for ammonia nitrogen control in aquaculture.